Gamma‐synuclein is a novel prognostic marker that promotes tumor cell migration in biliary tract carcinoma. (9th July 2021) - Takemura, Yusuke; Ojima, Hidenori; Oshima, Go; Shinoda, Masahiro; Hasegawa, Yasushi; Kitago, Minoru; Yagi, Hiroshi; Abe, Yuta; Hori, Shutaro; Fujii‐Nishimura, Yoko; Kubota, Naoto; Masuda, Yuki; et al.
Abstract: Gamma‐synuclein (SNCG) promotes invasive behavior and is reportedly a prognostic factor in a range of cancers. However, its role in biliary tract carcinoma (BTC) remains unknown. Consequently, we investigated the clinicopathological significance and function of SNCG in BTC. Using resected BTC specimens from 147 patients with adenocarcinoma (extrahepatic cholangiocarcinoma [ECC, n = 96]; intrahepatic cholangiocarcinoma [ICC, n = 51]), we immunohistochemically evaluated SNCG expression and investigated its correlation with clinicopathological factors and outcomes. Furthermore, cell lines with high SNCG expression were selected from 16 BTC cell lines and these underwent cell proliferation and migration assays by siRNAs. In the results, SNCG expression was present in 22 of 96 (22.9%) ECC patients and in 10 of 51 (19.6%) ICC patients. SNCG expression was significantly correlated with poorly differentiated tumor in both ECC and ICC ( p = 0.01 and 0.03, respectively) and with perineural invasion and lymph node metastases in ECC ( p = 0.04 and 0.003, respectively). Multivariate analyses revealed that SNCG expression was an independent poor prognostic factor in both OS and RFS in both ECC and ICC. In vitro analyses showed high SNCG expression in three BTC cell lines (NCC‐BD1, NCC‐BD3, and NCC‐CC6‐1). Functional analysis revealed that SNCG silencing could suppress cell migration in NCC‐BD1 and NCC‐CC6‐1 and downregulate cell proliferation in NCC‐CC6‐1 significantly. In conclusion, SNCG may promote tumor cell activity and is potentially a novel prognostic marker in BTC. Abstract : This study revealed for the first time the clinicopathological roles of gamma‐synuclein (SNCG) in biliary tract carcinoma (BTC). SNCG was identified as a strong independent poor prognostic factor of overall and recurrence‐free survival and was also significantly correlated with poor differentiation and perineural invasion in BTC.